PENYEBAB TINGGINYA KARIES GIGI PADA WANITA USIA 15 – 44 TAHUN DI DESA GONDOSARI WILAYAH KERJA PUSKESMAS GONDOSARI KABUPATEN KUDUS - Rizki Fitriana Noor; Ani Subekti; Yodong Yodong; Bambang Sutomo (Jurnal Kesehatan Gigi, 2015)
TITLEThe causes of dental caries enhancement in women aged 15-44 years old in Gondosari village of Puskesmas Gondosari, Kudus working areaABSTRACTCaries is a disease of hard dental tissue caused by the activity of a microorganism in a carbohydrate that is fermented. The signs are the demineralization of dental hard tissue damage followed by organic material. Caries are caused by factors inside and outside factors. Women are generally more susceptible to dental problems because of hormonal changes they experience. Hormonal changes that affect blood flow to the gum tissue and also affect the body's response to toxins produced by plaque and bacteria (microorganisms) that cause caries.This research is a descriptive cross sectional study design form that take measurements or observations with the sample 83 women aged 15-44 years in the village of Gondosari. Data collection was performed by means of direct examination to women regarding salivary pH, viscosity of saliva, and saliva hydration and administration of questionnaires that include environmental factors, behavior, health care and offspring. The data obtained were analyzed by quantitative descriptive analytic and prioritized using ultrasound.Saliva hydration factor is a factor of the cause of dental caries is the most dominant at 79%, followed by saliva pH and viscosity of saliva. While behavioral factors are external factors, the most dominant cause of dental caries, followed by the environment, health and heredity. Suggested searching for information about oral health and increase awareness and consciousness, attention to social behavior, following the extension, and pay attention to the health of teeth and mouth with healthy teeth and mouth checked regularly every six months and do fillings in cavities. Keywords :  Causes of caries, Women Age 15-44 Years